2015
DOI: 10.5173/ceju.2015.647
|View full text |Cite
|
Sign up to set email alerts
|

Durability, safety and efficacy of polyacrylamide hydrogel (Bulkamid®) in the management of stress and mixed urinary incontinence: three year follow up outcomes

Abstract: IntroductionThere are a myriad of treatment options available for patients suffering with the increasingly prevalent condition of stress urinary incontinence (SUI). The minimally invasive nature of periurethral bulking agents makes them an attractive proposition in the correctly selected patient. There is, however, limited data available on the medium to long term safety and efficacy of this procedure. The aim of our study is to evaluate the outcomes of Polyacrylamide Hydrogel (PAHG) (Bulkamid®) as a periureth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Bulking therapy is simple, safe, and shows both objective and subjective improvement and relief in selected SUI patients [ 10 ]. Although a Cochrane Review concluded that evidence for urethral injection therapy to treat UI in women remains insufficient to guide practice [ 18 ], the minimally invasive nature, efficacy, and safety of periurethral bulking with PAHG favors its use in the correctly selected patient [ 19,20,21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bulking therapy is simple, safe, and shows both objective and subjective improvement and relief in selected SUI patients [ 10 ]. Although a Cochrane Review concluded that evidence for urethral injection therapy to treat UI in women remains insufficient to guide practice [ 18 ], the minimally invasive nature, efficacy, and safety of periurethral bulking with PAHG favors its use in the correctly selected patient [ 19,20,21 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 Three studies present shorter follow-up data of standard PAHG injection with a timeline similar to our study. 20,21,23 However, comparison continues to be limited by differing definitions of subjective and objective outcomes, methods of data collection, and varying sample sizes. Pai et al 23 offer a retrospective study of 212 women and report 82.8% subjective improvement (defined as subjective cure or significant improvement) at 3-month follow, which was stable over the 5-year study.…”
Section: Discussionmentioning
confidence: 99%
“…Bulkamid ® is an injectable synthetic polyacrylamide hydrogel approved by the FDA for use in the United States in 2020 to treat stress urinary incontinence (SUI) by functioning as a bulking agent to add a total volume of up to 2 ml to the walls of the urethra ( U.S. Food and Drug Administration, 2021 ; Kasi et al, 2016 ). In vitro and in vivo studies investigated the cytotoxicity ( McCollister et al, 1965 ) and degradation ( Caulfield et al, 2002 ) of polyacrylamide, informing the choice of the 2.5% (w/v) polyacrylamide concentration that was confirmed via multiple long-term clinical studies to be suitable in the targeted application ( Lose et al, 2010 ; Pai and Al-Singary, 2015 ; Kasi et al, 2016 ). Although polyacrylamide was not previously approved for clinical use by the FDA, it had been in clinically used for breast augmentation in China since 1997 and years earlier in Ukraine ( Margolis et al, 2015 ), albeit with reports of multiple adverse complications such as lumps, breast pain and induration, and in certain cases a foreign body response which destroyed the structure of adjacent muscle and gland ( Qiao et al, 2005 ).…”
Section: Clinical Translation Of Hydrogelsmentioning
confidence: 99%